Efficacy of abbreviated progressive muscle relaxation and active relaxation training on improvement of attentiveness mediated by transient feeling and psychobiological indices of anxiety - Mei, Chan Sue (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
The present study was undertaken with an objective to determine differential efficacy of psychotherapeutic interventions, namely abbreviated progressive muscle relaxation (APMR) exercise training and active relaxation in enhancing attentive capacity in young active female participants. Twenty seven female students of Universiti Sains Malaysia in the age ranging from 18 to 24 years volunteered as participants, who were assessed with dispositional and transient anxiety by employing Spielberger's State and Trait Anxiety Inventory (ST AI). Thereafter, they were randomly categorized into three groups; viz. - Group A- control group; Group B - participants received training of APMR and Group C - participants received training of Active relaxation. All of the participants were subjected to evaluation of transient anxiety; both simple and complex reaction ability; psychobiological measures of tonic and phasic skin conductance activity as measure of pre-intervention analyses. Thereafter the participants of intervention conditions were introduced to their respective intervention training progran1s following standardized protocol (15 minutes/day; 2 days/week for 6 weeks). Mid-term analyses (all of the parameters of pre-intervention analyses were repeated) were done three weeks after the introduction of intervention sessions. Thereafter the similar protocol of intervention was followed for three more weeks. Thereafter all of the participants were assessed once again for the post-intervention analyses (following similar analyses protocols). Findings of the analyses suggested that both APMR and active relaxation intervention had beneficial impacts on attentive performance, characterized by psychomotor simple muscular reaction time and on cognitively dominated complex reaction performance. Furthermore, both of the interventions have been observed to result in alteration in the psychobiological make-up of the participants, which finally resulted in improvements in attentive performances.